Isolated Large Glenoid Fracture in Acute Glenohumeral Dislocation in the Elderly: A Novel Indication for Reverse Shoulder Arthroplasty - Tyler Smith; Joseph D’Alonzo; Alfonso Arevalo; Jack Kazanjian (Case Reports in Orthopedics)
Case. Two elderly males presented with traumatic shoulder dislocation and bony Bankart fracture consisting of greater than 25% of the glenoid width. Due to several concomitant factors such as polytrauma, activity level, rotator cuff pathology, optimization of comorbidities, risk of complications, and potential for revision surgery, the patients were treated with reverse shoulder arthroplasty (RSA). Conclusion. RSA may be a satisfactory treatment option for isolated, large glenoid fractures associated with anterior glenohumeral instability in the elderly. These patients are susceptible to rapid deconditioning with prolonged immobilization and may not be medically suited to undergo the prolonged recovery period associated with open reduction internal fixation or potentially undergo revision operations.